Sea Phenomenon in Perspective Science and Religion (Islam) - Khilma Novia Amalina (Kaunia: Integration and Interconnection Islam and Science, 2017)
Natural phenomena in recent years continuously emerging as the development of a modern era. One of these natural phenomena is discovery an undersea river Cenota Angelita in Mexico. There are Vertebrates and Invertebrates animal in various forms between a confluence two streams. These discoveries make curious various parties further examine both science and religious. This paper will explain the phenomenon of the sea from science and religion perspective by using literature study in qualitative-descriptive method. Thus, the sea is one of the things God created with various benefits and phenomena. The existence of verses that explain the phenomenon of the sea, shows the existence of harmony between Al-Qur'an and science.